Pembinaan Kader Kesehatan di Pondok Pesantren Darul Abror dan Al-Falah Biru Kabupaten Garut - Yusni Ainurrahmah; Ridwan Riadul Jinan; Fauzan Zein Muttaqin; Raden Siti Jundiah; Agustina Suryanah; Pujiati Setyaningsih (Jurnal Abdimas Kesehatan (JAK), 2023)
Sanitation conditions in Islamic boarding schools are closely related to infectious diseases, namely acute respiratory infections and scabies. Islamic boarding schools in Garut Regency that are currently developing, namely Darul Abror and Al Falah Biru Islamic boarding schools. transmission of disease and delays in handling if the student is sick or has an accident. The solution in this community service is through educational activities on Clean and Healthy Behavior, First Aid for Accidents, initiation of the establishment of the Islamic Boarding School Health Post and fostering health cadres to manage the Poskestren. The purpose of this activity is to increase the knowledge of the students, as well as to have health cadres for the students who handle the students through the poskestren. The method used is participatory method. This community service activity includes a preliminary survey, coordination with boarding school administrators, preparing supporting equipment. The activity continued with the health education stage and an approach based on mobilizing the role of the pesantren community, namely teachers, caregivers for students and students. The activity ended with an evaluation of educational material. The results of distributing the questionnaires found that there was an increase in knowledge after education about PHBS, P3K and Poskestren at the Darul Abror and Al Falah Biru Islamic Boarding Schools.